Geometric fractional Brownian motion perturbed by fractional Ornstein-Uhlenbeck process and application on KLCI option pricing - Alhagyan, Mohammed; Misiran, Masnita; Omar, Zurni (2016)
This paper presents an enhanced model of geometric fractional Brownian motion where its volatility is assumed to be stochastic volatility model that obeys fractional Ornstein-Uhlenbeck process.The method of estimation for all parameters (α, β, m, μ, H1, and H2) in this model is derived.We calculated the value of European call option using the estimates based on the methods of Masnita [1] [2] and Kukush [3], traditional Black-Scholes European option price, in addition to proposed model in order to make comparison study.